Coupling CFD model and FEM model to investigate the impact of debris flows on a low-rise building - Thi Thu Hien Le; Van Chien Nguyen; Duc Toan Nguyen; Duc Thanh Tran (Results in Engineering)
This study integrates a hydrodynamic model with a structural analysis model to investigate the behavior of a reinforced concrete (RC) frame building under the influence of various hydrodynamic variables, such as debris flow materials, flow intensity, and flow direction. The impact force generated during the first phase of fluid-structure interaction is significantly larger around (20 ÷ 30) % than that in the steady phase, resulting in a substantially bigger maximum value of bending moment (Mmax) and displacement (δ) in every RC column. An increase in flow intensity and solid concentration leads to a larger impact load, resulting in higher values of Mmax and δ. Furthermore, the flow that passes through the porous exterior of the house poses a greater risk than the flow that affects the non-porous side of the house. By comparison with two Vietnamese standards of bending moment and displacement, all columns of the target building are susceptible to collapse in all scenarios when taking into account the bending moment. Nevertheless, in relation to the key threshold of displacement, the building is likely to remain secure.